Afghanistan Development Update, November 2017 - World Bank (World Bank, Washington, DC, 2017)
Afghanistan’s security environment is continuing to deteriorate. The increased conflict appears to be holding back business and consumer confidence from recovering fully from the impact of the security transition in 2014. Economic growth has increased moderately from 2014-15, when the lowest growth rate was recorded since 2003. Proxy data for the first half of 2017 indicates that economic activity is continuing to languish, while business sentiment, gauged from the quarterly business perception surveys, appears to have improved slightly between the first and second quarters of 2017, though it remains lower than in the second quarter of 2016. The annual economic growth rate is projected to reach 2.6 percent in 2017, increasing very slightly from the figure of 2.2 percent recorded in 2016. Growth is projected to edge up to 3.2 percent in 2018, assuming no further deterioration in the security environment. While this constitutes a moderate improvement compared to 2014 and 2015, it is still significantly below the 9.6 percent average annual rate recorded in the period from 2003 to 2012.